Metformin for Gestational Diabetes: Is it effective? - Cabral, Juliano da Silva; Ferrer, Alan Oliveira; Paula, Jussara Miranda de; Felzener, Manoel Carlos Melillo (Seven Editora, 2023)
Gestational Diabetes Mellitus is a pathology related to increased insulin resistance and glucose intolerance, with changes in blood glucose detected for the first time during the gestational period. Faced with these situations, several therapies are considered, insulin being considered the gold standard, but with recognition of new options involving oral drugs, such as metformin. The objective was to discuss the effectiveness of the use of metformin against gestational diabetes. This is an integrative literature review, through a search in the MEDLINE, LILACS databases, via the VHL and SciELO, using the Health Sciences Descriptors: Pregnancy, Diabetes and Metformin, in association with the Boolean operator “AND”. A total of 16 studies were reached to compose the review. The use of metformin generated positive results, such as lower total cholesterol, uric acid and microalbuminuria, lower risks of premature birth and the development of congenital anomalies, helped with postprandial blood glucose, lower maternal weight gain and avoided maternal hypoglycemia. and neonatal. The general effectiveness is proven, however it is still a topic that needs further studies, as it also presents negative results and can lead to maternal and fetal complications, since metformin is a medication that crosses the placenta, which can lead to fetal harm. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-155